Competitive Dynamics in Micro: Analysis of Perception About Competition in Unitomo Street Food Business - Purnomo, Bambang Raditya (Sinergi : Jurnal Ilmiah Ilmu Manajemen, 2017)
The purpose of the study this is to explore small and micro businesses in their connections with competitors and the competitive force in the market.  This study uses the information processing approach to examine three activities, scanning the competitive environment, the interpretation of competitive actions, and reactions based on that assessment.  This research is motivated by the lack of competitiveness of micro businesses, especially those engaged in the culinary field.  This study uses qualitative approach with phenomenological methods, in which  researchers try to explain or reveal the meaning of a concept or phenomenon of experience based on the awareness that occurs in some individuals.  In this study, researchers collect, summarize and interpret the data obtained, which is then processed back in order to obtain a clear, directed and thorough pictures of the problem which become the object of research.  Phenomenological approach is used to analyze the original data collected from interview with the informant. Structural interpretation of the experience described by researchers in the description of the participants.